4r+7=-43

Simple and best practice solution for 4r+7=-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4r+7=-43 equation:


Simplifying
4r + 7 = -43

Reorder the terms:
7 + 4r = -43

Solving
7 + 4r = -43

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 4r = -43 + -7

Combine like terms: 7 + -7 = 0
0 + 4r = -43 + -7
4r = -43 + -7

Combine like terms: -43 + -7 = -50
4r = -50

Divide each side by '4'.
r = -12.5

Simplifying
r = -12.5

See similar equations:

| n^2+n=2n | | 7h-10=-4 | | -1-7x-6(-7-x)=36 | | (2a+4b)(3a-b)=0 | | 7h-10=4 | | (7a-7)(6a-4)= | | (7a-7)(6a-4)= | | 4p+7p^2= | | 3g+14=-7 | | (-90)+(-56)= | | 7x-8y=21+40 | | 3g+14=7 | | 1-sqrt(2x-4)=sqrt(5-x) | | 4y+4y+13=90 | | 3(2x^2+3)=4(2x+3) | | 2d-5=-13 | | 5x+20=7x+2 | | 2r+3s=1 | | 3x+1x-7= | | 31=-11x+3-x^2 | | 3/4x+6=-9 | | (-10)(-2)= | | 1/8(6t-8)=t+8/16 | | 5(3-w)+3=-3(w-4)-8 | | 1+qwertyuiop=9 | | x^2-XM-m^2=0 | | 3x+2x+1x+12=18 | | 0.90x+0.05(2-x)=0.10(92) | | 28-15= | | (-54)+17= | | 5m^2+12m-200=-3m | | -5b+3b-10=2 |

Equations solver categories